PENGARUH LITERASI ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PESERTA DIDIK KELAS XI SMA ADABIAH 2 PADANG - Wardana, Rizky; Hidayati, Abna; Kurnia, Reni; Masriani, Elsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) literacy on the critical thinking skills of eleventh-grade students at SMA Adabiah 2 Padang. The background of this study is that the use of AI among students has been high, but it has not been accompanied by adequate AI literacy, which potentially hinders the development of critical thinking skills. This research uses a quantitative approach with a survey method. The population consisted of all Phase F (Class XI) students at SMA Adabiah 2 Padang, with a sample of 175 students selected through proportional random sampling. Data were collected using a Likert-scale questionnaire instrument that had been validated and declared reliable. Data analysis used simple linear regression, which was preceded by normality, linearity, heteroscedasticity, and autocorrelation tests. The results showed that AI literacy had a positive and significant effect on students' critical thinking skills, with a t-value of 5.455 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) obtained was 0.147, meaning that AI literacy contributed 14.7% to the variation in students' critical thinking skills. The remaining 85.3% was influenced by other factors outside this study. This finding confirms that adequate AI literacy encourages students to interact critically and reflectively with AI systems, thereby strengthening their analytical, evaluative, and inferential thinking skills.